Tinjauan Perpajakan atas Transaksi Penjualan Rumah Bersubsidi di PT Anugrah Pratama Gowa - Nasruddin, Miftah; Ilham, Ilham; Sari, Sri (Income Journal: Accounting, Management and Economic Research, 2023)
The purpose of this study is to determine the calculation, deposit and reporting of Income Tax article 4 paragraph 2 and Land and Building Tax on subsidized house sales transactions at PT Anugrah Pratama Gowa, to determine Value Added Tax reporting on subsidized house sales transactions at PT Anugrah Pratama Gowa. The data analysis technique in this research is qualitative data analysis. The results of the research conducted show that: (1) PT Anugrah Pratama Gowa carries out the Calculation of Income Tax Article 4 paragraph 2 with a 1% tariff in accordance with Law Number 34 of 2016 concerning Income Tax on Income from the Transfer of Rights to Land and/or Buildings, and Sale/Purchase Binding Agreement on Land and/or Building and its Amendments. Article 4 paragraph 2 income tax deposit is made electronically by making an e-billing no later than the 10th of the following month. Article 4 paragraph 2 income tax reporting is reported before the 20th of the following month and declared as reported every time a payment has been made. (2) PT Anugrah Pratama Gowa implements Land and Building Tax Calculation by the Regional Revenue Service by imposing a 0.1% tariff. Land and Building Tax shall be deposited by each Taxpayer with a Tax Return (SPPT) issued by the Regional Government. Land and Building Tax Reporting occurs when the taxpayer has paid the tax due at the Bank or Post Office. (3) PT Anugrah Pratama Gowa is exempted from the imposition of Value Added Tax but still reports its Value Added Tax by issuing a Tax Invoice with code 008 for Value Added Tax exemption. The policy given by the government regarding taxes on subsidized house sales transactions provides relief for people who want to buy subsidized houses.